2021
DOI: 10.7759/cureus.16165
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Gastric Variceal Hemorrhage Secondary to Idiopathic Sinistral Portal Hypertension

Abstract: Sinistral portal hypertension (SPH), also known as left-sided portal hypertension or segmental portal hypertension, is a rare cause of upper gastrointestinal bleeding. Historically, SPH is a result of obstruction of the splenic vein often secondary to pancreatic pathology. To our knowledge, there are no reported cases of idiopathic SPH in which the findings cannot be attributed to any etiology. It is important to do a detailed workup to rule out common pathologies of SPH before making a diagnosis of idiopathic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…SPH is an extremely rare clinical entity characterized by elevated splenoportal pressure due to SVT 7 , 8 or obstruction. 9 Unlike conventional portal hypertension, SPH presents with a patent-extrahepatic portal vein 6 , 10 and normal liver function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SPH is an extremely rare clinical entity characterized by elevated splenoportal pressure due to SVT 7 , 8 or obstruction. 9 Unlike conventional portal hypertension, SPH presents with a patent-extrahepatic portal vein 6 , 10 and normal liver function.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 11 , 12 Splenoportal hypertension is commonly associated with pancreatic disorders such as acute pancreatitis, chronic pancreatitis, PPs, pancreatic neoplasms, and pancreatic surgery. 7 , 8 , 10 , 11 …”
Section: Discussionmentioning
confidence: 99%
“…For instance, some studies have reported that sinistral portal hypertension could induce pancreatic adenocarcinoma 14 , 15 . Another study discloses that sinistral portal hypertension could lead to gastric variceal hemorrhage 16 . Therefore, the timely management of sinistral portal hypertension is important 17 , 18 .…”
Section: Discussionmentioning
confidence: 99%
“…LSPH patients suffer from gastric varices (GVs) associated with abnormal dilatation of the gastric venous system to return excess splenic blood to the liver, leading to massive bleeding and mortality (4,5). Although balloonoccluded retrograde transvenous obliteration (BRTO) or endoscopic injection sclerotherapy (EIS) are often performed for GVs associated with cirrhotic portal hypertension, BRTO or EIS are not suitable for GVs associated with LSPH be-cause of their vascular anatomy and hemodynamics (1,5).…”
Section: Introductionmentioning
confidence: 99%